Comparison of Linear Dimensional Accuracy Between One Step and Two-step Impression Technique Using Polyvinyl Siloxane Impression Material - Dad, Khuda-E-; Yazdanie, Nazia; Hussain, Shafqat; Waqas, Mohammad; KUMAR, KAPIL; Malik, Haider Amin (Journal of Gandhara Medical and Dental Science, 2022)
Objectives: This study compares the linear dimensional accuracy between one step and two-step impression techniques using polyvinyl siloxane impression material. Methodology: The Randomized controlled trial was done in the Department of Prosthodontics, FMH College of Medicine and Dentistry Lahore and Pakistan Council for Science and Industrial Research Lahore. All impression samples which fall under the inclusion criteria in the Department of Prosthodontics, FMH College of Medicine and Dentistry Lahore and Pakistan Council for Science and Industrial Research Lahore were included. Samples were divided into two groups, i.e., Group 1 (single-step technique) & Group 2 (two-step technique). The impression’s longitudinal length and inter-line distance were measured to assess the outcome i-e linear dimensional accuracy. Result: A total of 60 impression samples with polyvinyl siloxane impressions material were made. The linear dimensional accuracy in one step & two-step impression technique was seen in 5 (8.33%) & 13(21.66%) samples, respectively, (p=0.011). Conclusion: Compared to the one-step impression technique, the higher linear dimensional accuracy of the two-step impression technique uses polyvinyl siloxane impression material.